Yield Potential of Landraces of Maize in Sudan and the Avenues for their Genetic Improvement - K. Mesekal, Silvestro; S. Ibrahim, Abu Elhassan; M. Nour, Abdellatif (Gezira Journal of Agricultural Science; Vol 1 No 1 (2003), 2021)
The study was conducted for two years (1998-1999), during the rainy season, at the Gezira Research Station (GRS) of the Agricultural Research Corporation (ARC) of the Sudan, to identify some yield components for improving the yield levels and to determine the genetic factors influencing the yield parameters of six landraces of maize and their 15 single crosses produced by a 6 x 6 half diallel arrangement. The analysis of variance mean squares depicted significant ( P≤0.01) differences for most of the traits studied in both years, indicating high phenotypic variability. The best crosses giving grain yield above parental avterage were Hegeri  x Red, Sennar x Red and Hegeri x Ahmar Mahali with a range of 4098-4710 kg ha -l and 3014-3348 kg ha -1 in both cropping seasons, respectively. The best yielding parents were Ring-8 (4870 and 31 92 kg ha -l ) and Red (4658 and 3348 kg ha -l ) In 1998 and 1999, respectively. Strong, positive association exists between grain yield and days to 50% anthesis and silking, ear length, 100-seed  weight and grain per ear ranging from r = 0.54 * * (days to 50% silking) to r = 0.76 * * (ear length). Days to 50% anthesis and silking, plant and ear heights, 100-seed weight and ear length showed relatively high heritability estimates ranging between 21.91% - 65.33%. The analysis of variance mean squares due to GCA and SCA were significant (P≤0.0I) for most of the traits. The GCA: SCA ratio indicated that days to 50% anthesis, plant height, ear length, grain per ear and grain yield were controlled by additive genetic effects while days to 50% silking, ear height, ear per plant and 100-seed weight were largely influenced by non-additive genetic effects